2004
DOI: 10.1111/j.1365-2052.2004.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the bovine genes of the de novo AMP synthesis pathway1

Abstract: Summary The purine nucleotides adenosine monophosphate (AMP) and guanosine monophosphate (GMP) are critical for energy metabolism, cell signalling and cell reproduction. Despite their essential function, little is known about the regulation and in vivo expression pattern of the genes involved in the de novo purine synthesis pathway. The complete coding region of the bovine phosphoribosylaminoimidazole carboxylase gene (PAICS), which catalyses steps 6 and 7 of the de novo purine biosynthesis pathway, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This perfect conservation reveals a strong evolutionary constraint and provides evidence that this residue plays an important role in the stability or activity of the protein. Phosphoribosylformylglycinamidine synthase is involved in the fourth step of the de novo purine synthesis, a universal pathway among eukaryote organisms (with the exception of some para-sites) due to the central function of purine molecules in cell metabolism such as DNA and RNA synthesis and energy molecule supply (Henikoff, 1987;Bønsdorff et al, 2004). Although purine synthesis is a regulated balance between de novo and salvage pathways, it has been shown that de novo synthesis is more active in proliferating cells and therefore essential for meeting the high demand of purines for nucleic acid synthesis in early embryonic development (Alexiou and Leese, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This perfect conservation reveals a strong evolutionary constraint and provides evidence that this residue plays an important role in the stability or activity of the protein. Phosphoribosylformylglycinamidine synthase is involved in the fourth step of the de novo purine synthesis, a universal pathway among eukaryote organisms (with the exception of some para-sites) due to the central function of purine molecules in cell metabolism such as DNA and RNA synthesis and energy molecule supply (Henikoff, 1987;Bønsdorff et al, 2004). Although purine synthesis is a regulated balance between de novo and salvage pathways, it has been shown that de novo synthesis is more active in proliferating cells and therefore essential for meeting the high demand of purines for nucleic acid synthesis in early embryonic development (Alexiou and Leese, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The ATP consuming-generating system is open and consequently some AMP molecules are de novo biosynthesized [143] ; whilst a part of AMP does not continue in the reactive system due to its hydrolysis, forming adenine and ribose 5-phosphate [144] . Finally, according to experimental observations, we have considered that a very small part of ATP does not remain in the system, but is drained out from the cell [145] – [149] .…”
Section: Methodsmentioning
confidence: 99%
“…The phosphoribosylaminoimidazole carboxylase, phosphoribosylaminoimidazole succinocarboxamide synthetase ( PAICS ) gene encodes a bifunctional enzyme that has phosphoribosylaminoimidazole carboxylase activity in its N-terminal region and phosphoribosylaminoimidazole succinocarboxamide synthetase activity in its C-terminal region [ 3 ]. This enzyme catalyzes steps 6 and 7 of the de novo purine biosynthesis pathway (Phosphoribosyl pyrophosphate amidotransferase (PPAT) catalyses step 1; phosphoribosylglycinamide formyltransferase (GART) steps 2, 3 and 5; phosphoribosylformylglycinamidine synthase (PFAS) step 4; phosphoribosylaminoimidazole carboxylase (PAICS) steps 6 and 7; adenylosuccinate lyase (ADSL) step 8 and 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase (ATIC) steps 9 and 10) [ 4 ]. Thus, PAICS is a promising target for rational anticancer drug design [ 3 ].…”
Section: Introductionmentioning
confidence: 99%